Superior High‐Temperature Energy Density in Molecular Semiconductor/Polymer All‐Organic Composites - Zhang, Bin; Chen, Xiao‐ming; Pan, Zhe; Liu, Peng; Mao, Minmin; Song, Kaixin; Mao, Zhu; Sun, Rong; Wang, Dawei; Zhang, Shujun (Advanced functional materials, 2023)
High‐temperature dielectric polymers are in constant demand for the multitude of high‐power electronic devices employed in hybrid vehicles, grid‐connected photovoltaic and wind power generation, to name a few. There is still a lack, however, of dielectric polymers that can work at high temperature (> 150 °C). Herein, a series of all‐organic dielectric polymer composites have been fabricated by blending the n‐type molecular semiconductor 1,4,5,8‐naphthalenetetracarboxylic dianhydride (NTCDA) with polyetherimide (PEI). Electron traps are created by the introduction of trace amounts of n‐type small molecule semiconductor NTCDA into PEI, which effectively reduces the leakage current and improves the breakdown strength and energy storage properties of the composite at high temperature. Especially, excellent energy storage performance is achieved in 0.5 vol.% NTCDA/PEI at the high temperatures of 150 and 200 °C, e.g., ultrahigh discharge energy density of 5.1 J cm−3 at 150 °C and 3.2 J cm−3 at 200 °C with high discharge efficiency of 85–90%, which is superior to its state‐of‐the‐art counterparts. This study provides a facile and effective strategy for the design of high‐temperature dielectric polymers for advanced electronic and electrical systems. This study reports the novel all‐organic dielectric composite films of 1,4,5,8‐naphthalenetetracarboxylic dianhydride (NTCDA)/polyetherimide (PEI) by using a facile solution casting method. By judiciously introducing semiconducting NTCDA into PEI, electron traps are successfully constructed, effectively reducing the leakage current and improving the breakdown strength. Finally, excellent high‐temperature energy storage performance is achieved in 0.5 vol.% NTCDA/PEI at 150 and 200 °C.